A New Approach to the Romanization of Written Mongol - Balk, Michael; Janhunen, Juha (Studia Orientalia Electronica, 2014)
This paper has grown from a joint project which the two authors initiated in late 1997 on the Romanization of the Mongol script. The authors first met earlier the same year at the Seventh International Congress of Mongolists in Ulan Bator, where they presented individual papers on related topics (Balk 1997, Janhunen 1997). Since it turned out that the two papers reflected an almost identical understanding of the fundamental issues of the problem, the authors decided to continue the work together in order to create a unified system of Romanization for Written Mongol with a potential for wider use in both scholarly and practical contexts. The final results of this work, as well as the detailed discussions which preceded them, will appear as separate publications, in which the history of the question will also be given due consideration. The purpose of the present paper is to give an introduction to the principal considerations and motivations underlying the new approach to the Romanization of Written Mongol. At the same time, the actual solutions proposed by the authors will also be illustrated.